LEARNING IDIOMS TO SPEAK LIKE A NATIVE SPEAKER OF ENGLISH - Yo’lchiyeva Malika Ulug’bek qizi; Zohidova Guzal Elbekovna (TADQIQOTLAR, 2025)
Abstract: Mastering how natives actually talk requires understanding a culture’s unique phrases or idioms. The customized phrases are referred to as idioms, and these heady phrases are essential in developing proficiency in communication. This is an attempt to try to understand how to speak like a native speaker with learning idioms. In this paper, idioms are more common in daily conversations, their cultural importance and their relevance for communication is analyzed. The research is focused on the conclusion that an individual’s knowledge of idioms can greatly change their language proficiency and fluency.